TOWARDS HARMONY AND PEACE WITH NONHUMANS: Pandemics and Ecological Democracy in Greg Bear’s Darwin’s Children - Joo, Kee Wha (Journal of Dharma, 2021)
Due to rising interest in Anthropocene and the COVID-19 pandemic, this essay aims to explore the fictional viral pandemics and the posthuman society in Greg Bear’s Darwin’s Children through the lens of new materialism and puts forth Homo monstercus as a new image of humanity fit for new lifeform in the era of the pandemic. As a descendent of Homo sapiens, Homo monstercus is the new protagonist of the future Earth, monster-like humanity, constantly transforming and evolving to survive the Anthropocene in harmony and peace with nonhumans. By applying theories such as Gilbert Simondon’s individuation theory and Bruno Latour’s actor-network theory and using concepts such as Karen Barad’s intra-action, Stacy Alaimo’s trans-corporeality, Donna Haraway’s companion species, this paper analyzes the anthropocentric relationship with nonhumans, divulges ecological and democratic ethic which enables their harmonious coexistence and symbiosis.